Postoperative morbidity differences between proximal and distal knee saphenous harvesting in coronary artery bypass graft surgery - Ismail Selçuk (Digital ProScholar Media, 2021)
Objectives. Coronary artery bypass grafting (CABG) is the most common procedure in cardiac surgery and the great saphenous vein (GSV) are the preferred conduits. The effects of saphenous vein incision (SVI) harvesting site choice on SVI wound complications, pretibial edema, and the need for compression stockings were evaluated retrospectively in patients undergoing CABG surgery. Materials and Methods. A total of 1900 patients operated for CABG between 2003 and 2021 in our clinic were included in this study, with GSV harvest performed at below-knee level (Group-A, n:841) and above-knee level (Group-B, n:1059). SVI was made 2 cm superior and 1 cm anterior to the medial malleolus in group-A; and 3 cm superior to medial epicondyle, extending to 3 cm inferior to the inguinal ligament in group-B. Examination for edema was made with 4-5 seconds of thumb pressure at the ankle level, then the depth of the pit was measured. Results. Ankle edema (Group-A n:132, Group-B n:25), the use of compression stockings (Group-A n:97, Group-B n:13), and paresthesia (Group-A n:51, Group-B n:10) were different between the two groups and the differences were statistically significant. However, prolonged wound healing (Group-A n:11, Group-B n:38), superficial wound infection (Group-A n:6, Group-B n:11), hematoma (Group-A n:4, Group-B n:9), and lymphorrhea (Group-A n:4, Group-B n:7) incidences were not statistically different between the two groups. Conclusions. Among patients with GSV extracted using the open conventional surgery technique, pretibial edema, paresthesia, and compression stocking use were observed less frequently in patients with preoperative doppler-ultrasonography evaluation and above-knee saphenous harvest.